2016
DOI: 10.1155/2016/6951091
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Reduced Microbial Diversity in Inflammatory Bowel Disease

Abstract: A considerable number of studies have been conducted to study the microbial profiles in inflammatory conditions. A common phenomenon in inflammatory bowel disease (IBD) is the reduction of the diversity of microbiota, which demonstrates that microbial diversity negatively correlates with disease severity in IBD. Increased microbial diversity is known to occur in disease remission. Species diversity plays an important role in maintaining the stability of the intestinal ecosystem as well as normal ecological fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 91 publications
5
43
0
1
Order By: Relevance
“…In young bats, the microbial KOs were reduced after AstV-infection whereas they were increased in adult bats. The reduction in microbial KOs might be due to a less efficient gut bacterial community (e.g., reduction in abundance of butyrate producing bacteria) in AstV+ young bats, similar to the observations in IBD [58], whereas the increase in overall KOs in adult AstV + bats could be related to an overall increase in bacterial diversity. Accordingly in adults, several predicted bacterial metabolism pathways changed in abundance after AstV-infection.…”
Section: Discussionsupporting
confidence: 75%
“…In young bats, the microbial KOs were reduced after AstV-infection whereas they were increased in adult bats. The reduction in microbial KOs might be due to a less efficient gut bacterial community (e.g., reduction in abundance of butyrate producing bacteria) in AstV+ young bats, similar to the observations in IBD [58], whereas the increase in overall KOs in adult AstV + bats could be related to an overall increase in bacterial diversity. Accordingly in adults, several predicted bacterial metabolism pathways changed in abundance after AstV-infection.…”
Section: Discussionsupporting
confidence: 75%
“…The induction of leaky gut by gut in ammation accelerates the absorption of bacterial byproducts, such as LPS, into the blood and alters the gut microbiota composition, which is termed dysbiosis [20][21][22]. Patients with IBD, including UC and CD, exhibit a reduced gut microbial diversity compared with healthy individuals [23][24][25]. Lepage et al reported that patients with UC exhibit the increased Actinobacteria and Proteobacteria populations compared with their healthy siblings [26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we observed a decreased diversity in the repertoire of anti-bacterial IgG in CD patients compared with healthy controls and UC patients. The lower diversity of anti-bacterial IgG likely reflects the decreased microbial diversity reported in CD patients (Andoh et al, 2012;Quince et al, 2015;Gong et al, 2016). We observed an increased reactivity of antibodies to fucosylated oligosaccharides and commensal bacteria in the sera of CD patients, but not of UC patients.…”
Section: Discussionmentioning
confidence: 55%